Intelligent presentation slide control video (INSTRUCT) / Mohd Razif Shamsuddin, Nurzeatul Hamimah Abd Hamid and Muhammad Syafiq Jasmin - Shamsuddin, Mohd Razif; Abd Hamid, Nurzeatul Hamimah; Jasmin, Muhammad Syafiq (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Commonly people have been using mouse and keyboard as ways for them to control their slide presentation. This Human Computer Interaction technique has changed little since the introduction of both keyboard and mouse. However there is a next step of evolution that started to gain interest lately which is hand gesture recognition. With the help of webcam, human can interact with computer by using their hand gesture. With this technique we can substitute the use of mouse or keyboard to control slide presentation. This product aims to achieve this goal. A Neural Network Method and Convexity Defects Algorithm is used to enable the system to detect hand gesture without any additional hardware. The product uses an open computer vision library and is quite easy to use.